Pengaruh Air Kelapa Muda Terhadap Kadar Antiokidan Endogen Akibat Paparan Asap Rokok pada Tikus Jantan Galur Wistar - Siti Thomas Zulaikhah; Joko Wahyu Wibowo; Muhammad Sinatrio Budi Wibowo (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Smoke exposure causes an increase in lipid peroxidation, an increase in ROS, a decrease in glutathione levels and the activity of endogenous antioxidant enzymes such as glutathione peroxidase (GPx). Young coconut water contains compounds such as L-arginine, vitamin C, minerals and selenium that can increase endogenous antioxidants. The endogenous antioxidant parameter studied in this study was GPx. This study aims to determine the effect of young coconut water on endogenous antioxidant levels due to exposure to cigarette smoke in wistar rats. The design of this study was a posttest only control group. Twenty-four male wistar rats were used as 4 groups randomly, ie K1 was given standard diet et libitum + aquadest, K2 was given standard feed et libitum + aquadest + exposure to cigarette smoke 3 sticks/day, P1 was given standard feed et libitum + aquadest + exposure to cigarette smoke 3 cigarettes/day + vitamin E at a dose of 1.8 mg/200 g BW/day, P2 was given standard feed et libitum + aquadest + exposure to cigarette smoke 3 cigarettes/day + young coconut water at a dose of 8mL/200 gBW/day. The treatment was given for 14 days. On the 15th day, the rats were drawn blood to check the levels of GPx using ELISA (Enzyme-Linked Immunosorbent Assay), the data were analyzed using the One Way Anova test. Mean levels of GPx K1: 68.81±5.51 U/mL; K2: 33.96±3.13 U/mL; P1: 61.99±6.21 U/mL and P2: 57.49±4.92 U/mL. The results of the analysis showed a p value of 0.000, so it was concluded that young coconut water had an effect on the levels of endogenous antioxidants GPx in wistar strain rats exposed to cigarette smoke. Keywords: cigarette smoke; endogenous antioxidants; coconut water ABSTRAK Paparan asap menyebabkan peningkatan peroksidasi lipid, peningkatan ROS, penurunan kadar glutation dan aktivitas enzim antioksidan endogen seperti glutathione peroxidase (GPx). Air kelapa muda mengandung senyawa seperti L-arginin, vitamin C, mineral dan selenium yang dapat meningkatkan antioksidan endogen. Parameter antioksidan endogen yang diteliti dalam penelitian ini adalah GPx. Penelitian ini bertujuan untuk mengetahui pengaruh air kelapa muda terhadap kadar antioksidan endogen akibat paparan asap rokok pada tikus galur wistar. Desain penelitian ini adalah posttest only control group. Dua puluh empat tikus jantan galur wistar digunakan sebagai 4 kelompok secara random, yaitu K1 diberi pakan standar et libitum + aquadest, K2 diberi pakan standar et libitum + aquadest + paparan asap rokok 3 batang/hari, P1 diberi pakan standar et libitum + aquadest + paparan asap rokok 3 batang/hari + vitamin E dosis 1,8 mg/200 g BB/hari, P2 diberi pakan standar et libitum + aquadest + paparan asap rokok 3 batang/hari + air kelapa muda dosis 8mL/200 gBB/hari. Perlakuan diberikan selama 14 hari. Hari ke-15 tikus diambil darah untuk diperiksa kadar GPx menggunakan ELISA (Enzyme-Linked Immunosorbent Assay), data dianalisis menggunakan uji One Way Anova. Rerata kadar GPx K1: 68,81±5,51 U/mL; K2: 33,96±3,13 U/mL; P1: 61,99±6,21 U/mL dan P2: 57,49±4,92 U/mL. Hasil analisis menunjukkan nilai p 0,000, sehingga disimpulkan bahwa ir kelapa muda berpengaruh terhadap kadar antioksidan endogen GPx pada tikus galur wistar yang dipapar asap rokok. Kata kunci: asap rokok; antioksidan endogen; air kelapa muda